2019
DOI: 10.1108/pr-08-2017-0239
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of supervisor competence, perceived employee mobility, and abusive supervision

Abstract: Purpose In response to the call for deeper investigation of abusive supervision (Martinko et al., 2013), the purpose of this paper is to examine perceived supervisor competence and perceived employee mobility (an individual’s perception of his/her ability to obtain new employment) to better understand contextual and individual factors that potentially influence the degree of harmful supervisory behaviors experienced by employees. Design/methodology/approach Responses from 749 survey participants were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 74 publications
0
4
0
1
Order By: Relevance
“…When it comes to leaders , manifold leader characteristics have been studied. For instance, a variety of personality variables and traits such as low agreeableness (Breevaart & de Vries, 2017), low competence (Meglich et al, 2019), high entitlement (Whitman et al, 2013), high machiavellianism (Kiazad et al, 2010; Lyons et al, 2019; Wisse & Sleebos, 2016), high narcissism (Lyons et al, 2019; Nevicka et al, 2018), low neural executive control (Waldman et al, 2018), high perfectionism (Guo et al, 2020), and high psychopathy (Lyons et al, 2019; Mathieu & Babiak, 2016; Wisse & Sleebos, 2016) have been found to relate to destructive leadership. When it comes to compromised mental health, manifold aspects including alcohol abuse (Byrne et al, 2014), depression (Byrne et al, 2014; Dionisi & Barling, 2019; Tepper et al, 2006), emotional exhaustion (Fan et al, 2020; Walsh & Arnold, 2018), psychological distress (Y.…”
Section: A Process Model On Arousal and Destructive Leadershipmentioning
confidence: 99%
“…When it comes to leaders , manifold leader characteristics have been studied. For instance, a variety of personality variables and traits such as low agreeableness (Breevaart & de Vries, 2017), low competence (Meglich et al, 2019), high entitlement (Whitman et al, 2013), high machiavellianism (Kiazad et al, 2010; Lyons et al, 2019; Wisse & Sleebos, 2016), high narcissism (Lyons et al, 2019; Nevicka et al, 2018), low neural executive control (Waldman et al, 2018), high perfectionism (Guo et al, 2020), and high psychopathy (Lyons et al, 2019; Mathieu & Babiak, 2016; Wisse & Sleebos, 2016) have been found to relate to destructive leadership. When it comes to compromised mental health, manifold aspects including alcohol abuse (Byrne et al, 2014), depression (Byrne et al, 2014; Dionisi & Barling, 2019; Tepper et al, 2006), emotional exhaustion (Fan et al, 2020; Walsh & Arnold, 2018), psychological distress (Y.…”
Section: A Process Model On Arousal and Destructive Leadershipmentioning
confidence: 99%
“…A mobilidade de emprego diz respeito à avaliação feita por um colaborador sobre suas chances de conseguir um novo trabalho (Meglich, Valentine, & Eesley, 2019) ou "a medida em que os empregados sentem que possuem alternativas de emprego atrativas" (Tepper, 2000, p. 179, tradução nossa). A mobilidade de emprego pode afetar de maneira significativa a intenção de deixar o emprego, pois os colaboradores, ainda que percebam um desajuste com a organização, apenas optam pela saída caso acreditem que encontrarão um ambiente mais favorável em outro lugar (Morley, Wheeler, Gallagher, Brouer, & Sablynski, 2007).…”
Section: O Papel Moderador Da Mobilidade De Empregounclassified
“…Perceived mobility is a construct that concerns the assessment that an employee makes about their chances of getting a new job (Meglich, Valentine, & Eesley, 2019) or "the extent to which employees feel they have attractive employment alternatives" (Tepper, 2000, p.179). Perceived mobility can significantly affect the intention to leave employment, as even if employees do not perceive a mismatch with the organization, they just opt for the exit, if they believe that a better fit will be achieved by working in another organization (Morley, Wheeler, Gallagher, Brouer, & Sablynski, 2007).…”
Section: The Moderating Role Of Perceived Mobilitymentioning
confidence: 99%